2022
DOI: 10.1186/s12906-022-03511-6
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and integrative medicine perspectives among veteran patients and VHA healthcare providers for the treatment of headache disorders: a qualitative study

Abstract: Objective To evaluate veteran patient and provider perceptions and preferences on complementary and integrative medicine (CIM) for headache management. Background The Veterans Health Administration (VHA) has spearheaded a Whole Health system of care focusing on CIM-based care for veteran patients. Less is known about patients’ and providers’ CIM perceptions and preferences for chronic headache management. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The Migraine Disability Assessment (MIDAS), 39 is a 5-item, self-report measure of life disruption due to headache in the last 1 month. Cut points represent thresholds for little or no disability (0-5), mild disability (6-10), moderate disability (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and severe disability (21þ). The Headache-related disability inventory (HDI), 40 is a 25-item self-report questionnaire that assesses both the emotional and functional impact of headache on daily activities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Migraine Disability Assessment (MIDAS), 39 is a 5-item, self-report measure of life disruption due to headache in the last 1 month. Cut points represent thresholds for little or no disability (0-5), mild disability (6-10), moderate disability (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and severe disability (21þ). The Headache-related disability inventory (HDI), 40 is a 25-item self-report questionnaire that assesses both the emotional and functional impact of headache on daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Items are rated from 0 to 3 (0 ¼ not at all to 3 ¼ nearly every day) with total score ranging from 0 to 24 for the PHQ-8. The PHQ-9 provides thresholds for severity of depressive symptoms: none-minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27) depressive symptoms. The PHQ-8 has demonstrated exceptionally high correlation with the PHQ-9 (r ¼ 0.997) and identical cutoffs are advised.…”
Section: Treatment Acceptability the Client Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to behavioral providers with specialization in behavioral pain or headache treatments can be challenging, particularly in rural settings [ 40 ]. Therefore, patients may face limited options in behavioral treatment providers, resulting in limited behavioral treatment strategies that may not adequately address their specific treatment needs [ 41 , 42 ]. Recent studies have observed greater use of telemedicine for patients who receive specialty pain services in rural populations (12%) compared to urban patients (3%) [ 43 ].…”
Section: Mitigating Barriers and Improving Access To Carementioning
confidence: 99%